2013
DOI: 10.1177/1087057113497401
|View full text |Cite
|
Sign up to set email alerts
|

Perspective on the Discovery and Scientific Impact of p38 MAP Kinase

Abstract: It has now been almost 20 years since the discovery of p38 MAP kinase and its role in inflammatory cytokine synthesis through reverse pharmacology and its subsequent exploration as a potential target for autoimmune and other diseases. At the time of its discovery, the use of cell-based phenotypic screens to identify new molecular targets was at its infancy, and while p38 MAP kinase was not the first target to be identified this way, it provides a useful model for reviewing the pros and cons of this approach an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 60 publications
(73 reference statements)
0
23
0
Order By: Relevance
“…Type I IFN treatment results in activation of Rac1 and its downstream effectors including MAP kinase kinase 3 (MKK3), MAP kinase kinase 6 (MKK6) [92,93], and cytosolic phospholipase A2 [94,95]. In turn, these events provoke phosphorylation and activation of the p38 MAP kinase, an important mediator of the inflammatory response [96]. p38 MAP kinase activation leads to downstream MapKapK-2 and MapKapK-3 activation, contributing to type I IFN-dependent transcriptional regulation of ISGs.…”
Section: Crossregulation Between Tnf and Ifn Signalingmentioning
confidence: 99%
“…Type I IFN treatment results in activation of Rac1 and its downstream effectors including MAP kinase kinase 3 (MKK3), MAP kinase kinase 6 (MKK6) [92,93], and cytosolic phospholipase A2 [94,95]. In turn, these events provoke phosphorylation and activation of the p38 MAP kinase, an important mediator of the inflammatory response [96]. p38 MAP kinase activation leads to downstream MapKapK-2 and MapKapK-3 activation, contributing to type I IFN-dependent transcriptional regulation of ISGs.…”
Section: Crossregulation Between Tnf and Ifn Signalingmentioning
confidence: 99%
“…As reviewed by Young et al, p38 MAPK target molecules are first characterized by using p38 MAPK specific inhibitors, SB203580 and SB202190, and more recently in gene deletion mouse models. Inhibition/deficiency of p38 MAPKs causes changes in cell survival/apoptosis, proliferation, differentiation, migration, mRNA stability, and inflammatory response in different cell types (Young, 2013). Although a vast majority of the literature focus on p38α MAPK isofrom function, a significant number of studies have been conducted to demonstrate the different functions of the distinct isoforms of p38 MAPK, For instance, p38β MAPK contributes to regulate Store Operated Calcium Entry (SOCE) and permeability responses in endothelial cell and bladder cancer cell migration through STIM1 and Hsp27, respectively (Sundivakkam, Natarajan, Malik, & Tiruppathi, 2013; Yu et al, 2014).…”
Section: Cellular Function Of P38 Map Kinasesmentioning
confidence: 99%
“…It has been confirmed that MAPK system, which consists of a cluster of a serine/threonine protein kinases, including JNK1-3, ERK1-2, p38 MAPK, is one of the most classical signal transduction pathways (Derbal, 2014). Almost all eukaryotic cells possess multiple MAPK pathways, which generally regulate multiple cell activities in response to different stimuli (Peti and Page, 2013;Young, 2013). In this work, we demonstrated that the administration of NaHS significantly increased protein expression ratio of p-p38/p38 in C6 cells, implying that p38 MAPK activation is involved in NaHS-mediated apoptosis of C6 cells, which is in agreement with the previous investigations in other types of cancer (Perry et al, 2011;Lv et al, 2014).…”
Section: Discussionmentioning
confidence: 98%